Patients with triple-negative, JAK2V617F- and CALR-mutated essential thrombocythemia share a unique gene expression signature - Alimam, Samah (Blood Adv, 2021)
Approximately 10% to 15% of patients with essential thrombocythemia (ET) lack the common driver mutations, so-called “triple-negative” (TN) disease. We undertook a systematic approach to investigate for somatic mutations and delineate gene expression signatures in 46 TN patients and compared the results to those with known driver mutations and healthy volunteers. Deep, error-corrected, next-generation sequencing of peripheral blood mononuclear cells using the HaloPlex(HS) platform and whole-exome sequencing was performed. Using this platform, 10 (22%) of 46 patients had detectable mutations (MPL, n = 6; JAK2V617F, n = 4) with 3 of 10 cases harboring germline MPL mutations. RNA-sequencing and DNA methylation analysis were also performed by using peripheral blood mononuclear cells. Pathway analysis comparing healthy volunteers and ET patients (regardless of mutational status) identified significant enrichment for genes in the tumor necrosis factor, NFκB, and MAPK pathways and upregulation of platelet proliferative drivers such as ITGA2B and ITGB3. Correlation with DNA methylation showed a consistent pattern of hypomethylation at upregulated gene promoters. Interrogation of these promoter regions highlighted enrichment of transcriptional regulators, which were significantly upregulated in patients with ET regardless of mutation status, including CEBPβ and NFκB. For “true” TN ET, patterns of gene expression and DNA methylation were similar to those in ET patients with known driver mutations. These observations suggest that the resultant ET phenotype may, at least in part and regardless of mutation type, be driven by transcriptional misregulation and may propagate downstream via the MAPK, tumor necrosis factor, and NFκB pathways with resultant JAK/STAT activation. These findings identify potential novel mechanisms of disease initiation that require further evaluation.